Co‐administration of proton pump inhibitors and/or of steroids may be a risk factor for low trough concentrations of posaconazole delayed‐released tablets in adult patients with haematological malignancies. (19th August 2018) - Cojutti, Pier Giorgio; Candoni, Anna; Lazzarotto, Davide; Rabassi, Nicholas; Fanin, Renato; Hope, William; Pea, Federico
Abstract : Aims: The aim of this study was to determine clinical variables associated with posaconazole exposure among adult patients with haematological malignancies who received posaconazole tablets for prophylaxis of invasive fungal infections (IFIs). Methods: The study population included adult patients with haematological malignancies who received posaconazole delayed‐release tablets for prophylaxis of IFIs after induction chemotherapy for acute leukaemia or graft‐versus‐host‐disease (GVHD) complicating hematopoietic stem cell transplantation (HSCT) in the period January 2016–December 2017. Results: Sixty‐six consecutive patients with 176 posaconazole C min were included for evaluation in the study. Subtherapeutic posaconazole concentrations (< 0.7 mg l −1 ) were observed at least once in 33.3% of patients (22/66), and overall in 17.0% of therapeutic drug monitoring (TDM) episodes (30/176). At multilevel linear regression, use of PPIs ( P = 0.008), use of intermediate or high dose steroids (>0.7 mg kg −1 daily) ( P = 0.022) and male gender ( P = 0.025) were significantly associated with decreased C min, whereas time from starting therapy ( P = 0.032) was associated with increased C min in our patient population. Conclusion: Posaconazole exposure during treatment with delayed‐released tablet formulation may be affected by the use of PPIs and/or of intermediate or high dose steroids.